The dynamics of ultrastructural changes in compartment of the power supply of follicular endocrinocytes of the thyroid gland in the course of process of distant interaction with the transplanted tumor. - Khripkov, I. S. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. With the tumor pathology of different localization thyroid status of patients, which determines the effectiveness of treatment and the survival of patients with the oncologic pathology, substantially changes. The determination of the morphological bases of the maintenance of thyroid status against the cellular and subcellular levels due to the conditions for distant interaction with the tumor makes it possible to determine the system mechanisms of intercellular interactions due to the conditions for the development of oncologic pathology. Objective. The purpose of the present investigation was the study of state and dynamics of changes in the intracellular system of the power supply of follicular endocrinocytes of the thyroid gland before the process of distant interaction with the tumor before the experiment. Methods. As the experimental model of tumor we have used a model of the slightly differentiated solid adenocarcinoma of Guerin. Experiment carried out on the rats - the males of the line of Vistar as far as the mass 120 - 160 g. animals were divided beside 2 groups. First group - control. To the second group - transplanted the strain of the cells of Guerin's carcinoma by hypodermic injection beside the region thighs. Animals derived based on the experiment on 2, 4 and 12 weeks. Is carried out the cytotopographic and quantitative ultramicroscopic study of the dynamics of changes of the mitochondria of thyrocytes before the process of distant interaction with the transplanted tumor. Results. On 2 weeks of an increase in the transplanted tumor are noted the substantial changes in the ultrastructure of mitochondria, which are manifested before the decrease of the length of mitochondrial cristae, to the loss by them of lammelar structure. On 4 weeks of experiment is noted a change in cytotopographic of mitochondria, their concentration near the apical pole of cell occurs. Is observed the deformation of mitochondria with the loss of lammelar structure and the decrease of a quantity of cristae. Mitochondrial matrix is clarified. The mitochondria are arranged before the center section of the cell perinuclearly on 12 weeks of experiment. Is observed the decrease of length and a change of orienting the cristae, which are arranged in parallel relative to the long axis of mitochondria, the destruction of cristae occurs. Conclusion. A change in cytotopographic and quantity indicators of the mitochondria of follicular endocrinocytes of the thyroid gland in the course of the process of distant interaction with the transplanted tumor they testify about the early disturbance of the energy exchange of cell with the subsequent disturbance of the energy guarantee of a process of the resorption of colloid and the possible activation against the last stages of the mitochondrial way of the development of apoptosis.